Layered Catalysts
Patent Information
- Application Number
- JP2023565244
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-21
- Filing Date
- 2022-04-20
- Publication Date
- 2025-04-25
AI Technical Summary
The rising cost of palladium and the potential decline in platinum prices have made it challenging to maintain effective catalytic performance in three-way conversion (TWC) catalysts used in exhaust gas treatment systems, necessitating a cost-effective alternative that maintains or improves HC, CO, and NOx reduction efficiency.
A layered catalyst article is developed with a top layer containing palladium, platinum, and rhodium, supported on a carrier, and a bottom layer with palladium, to replace palladium in TWC catalysts, ensuring a palladium-to-platinum ratio greater than 1:1, with the platinum and rhodium co-supported in the top layer.
The layered catalyst article achieves equivalent or improved catalytic performance in reducing HC, CO, and NOx emissions, offering a cost-effective solution by utilizing platinum instead of palladium while maintaining or enhancing emission control.
Smart Images

Figure 00000027_0000 
Figure 00000027_0001 
Figure 00000027_0002
Abstract
Description
[Technical field]
[0001] The present invention relates to a layered Pt / Pd / Rh trimetallic catalyst article, an exhaust gas treatment system including the article, and a method of treating an exhaust gas stream using the layered catalyst article or the exhaust gas treatment system. [Background technology]
[0002] In order to meet emission standards for unburned hydrocarbons (HC), carbon monoxide (CO) and nitrogen oxides (NOx, e.g., NO and / or NO2) pollutants, catalytic converters containing three-way conversion (TWC) catalysts (hereinafter interchangeably referred to as TWC catalysts or TWC) have been utilized for several years. TWC catalysts are well known to simultaneously oxidize unburned hydrocarbons and carbon monoxide and reduce nitrogen oxides in the exhaust stream from internal combustion engines, particularly gasoline engines.
[0003] TWC catalysts utilize platinum group metals (PGMs) as catalytically active species. In particular, palladium is usually used as the main platinum group metal, together with a small amount of rhodium. In recent years, the supply shortage of palladium has become serious, and the price of palladium has been rising, about 2.6 times that of platinum, so the rising production cost has become a major challenge in the field of TWC catalysts. At the same time, the production number of diesel engine vehicles, in which diesel oxidation catalysts containing platinum as a catalytically active species are commonly used, is decreasing, so the price of platinum is expected to fall. Therefore, TWC catalysts containing platinum instead of at least a part of palladium are desirable to significantly reduce the cost of the catalyst. However, it is expected that the simple replacement of palladium with platinum will result in unfavorable or unsatisfactory catalyst performance. Over the past few decades, various TWC catalysts containing a certain amount of platinum have been developed.
[0004] As engine exhaust gas regulations become increasingly stringent, there is a continuing need to provide TWC catalysts that efficiently remove HC, CO and NOx and can be manufactured at low cost. Summary of the Invention [Problem to be solved by the invention]
[0005] It is an object of the present invention to provide a catalyst article which contains platinum in place of the amount of palladium used in TWC catalysts and has equivalent or even improved overall catalytic performance with respect to the reduction of HC, CO and NOx. [Means for solving the problem]
[0006] Thus, the present invention provides a) a top layer comprising a palladium component, a platinum component and a rhodium component, the palladium component, the platinum component and the rhodium component being present in supported form, and at least a portion of the platinum component and at least a portion of the rhodium component being co-supported on one or more supports; b) a bottom layer comprising a palladium component in supported form as the sole platinum group metal component; and c) a substrate carrying the top layer and the bottom layer; a layered catalyst article comprising: Here, the palladium component, calculated as elemental palladium, is supported in the top layer and the bottom layer in a ratio of greater than 1:1.
[0007] In another aspect, the present invention provides an exhaust gas treatment system comprising a layered catalyst article as described herein positioned downstream of an internal combustion engine.
[0008] In a further aspect, the present invention provides a method for treating an exhaust gas stream comprising contacting the exhaust gas stream with a layered catalyst article or an exhaust gas treatment system described herein. [Brief description of the drawings]
[0009] [Figure 1]FIG. 1A is a schematic diagram of a Pd / Rh bimetallic catalyst article having an exemplary layered configuration prepared according to Example 1; FIG. 1B is a schematic diagram of a Pd / Pt / Rh trimetallic catalyst article having an exemplary layered configuration prepared according to Example 2; and FIG. 1C is a schematic diagram of a Pd / Pt / Rh trimetallic catalyst article having an exemplary layered configuration prepared according to Example 3. [Diagram 2] 2A, 2B, 2C, and 2D are schematic diagrams of Pd / Pt / Rh trimetallic catalyst articles having exemplary layered configurations prepared according to Examples 4, 5, 6, and 7, respectively. [Diagram 3] 3A and 3B are schematic diagrams of Pd / Pt / Rh trimetallic catalyst articles having exemplary layered configurations prepared according to Examples 8 and 9, respectively. [Figure 4] FIG. 4 is a schematic diagram of a Pd / Pt / Rh trimetallic catalyst article having an exemplary layered configuration, prepared according to Example 10. [Diagram 5] FIG. 5 is a schematic diagram of a Pd / Pt / Rh trimetallic catalyst article having an exemplary layered configuration, prepared according to Example 11. [Figure 6] FIG. 6 is a schematic diagram of a Pd / Pt / Rh trimetallic catalyst article having an exemplary layered configuration, prepared according to Example 12. [Figure 7] FIG. 7 is a graph showing tailpipe HC emissions after treating the exhaust gas with a catalyst article according to an embodiment. [Figure 8] FIG. 8 is a graph showing tailpipe CO emissions after treating exhaust gas with a catalyst article according to an embodiment. [Figure 9] FIG. 9 is a graph showing tailpipe NOx emissions after treating the exhaust gas with a catalyst article according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will now be described in detail. It should be understood that the present invention can be embodied in various forms and should not be construed as being limited to the embodiments set forth herein.
[0011] The singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise. Terms such as "comprise," "include," and "comprises" are used interchangeably with "contain," "contains," and the like, and are to be interpreted in an open-ended manner, i.e., additional components or elements may be present, for example. The phrases "consisting of" or "consisting essentially of" or synonyms may be subsumed within "comprise" or synonyms.
[0012] According to one aspect of the present invention, a) a top layer comprising a palladium (Pd), platinum (Pt) and rhodium (Rh) component, the palladium, platinum and rhodium components being present in supported form, with at least a portion of the platinum and at least a portion of the rhodium components being co-supported on one or more supports; b) a bottom layer comprising a palladium component in supported form as the sole platinum group metal component; and c) a substrate carrying the top layer and the bottom layer; A layered catalyst article is provided, comprising: Here, the palladium component, calculated as elemental palladium, is supported in the top layer and the bottom layer in a ratio of greater than 1:1.
[0013] The layered catalyst articles according to the present invention are particularly useful as TWC catalysts.
[0014] As used herein, the terms "palladium component," "platinum component," and "rhodium component" are intended to represent the presence of these platinum group metals in any possible valence state, which may be, for example, the respective metals or metal oxides in catalytically active form, or may be respective metal compounds, complexes, etc. that decompose or are otherwise converted to the catalytically active form, for example, by calcination or use of a catalyst.
[0015] As used herein, the term "layered catalyst article" refers to a catalyst article that includes a catalyst composition coated on a substrate in a layered design.
[0016] In some embodiments, the top layer in a layered catalyst article according to the invention is substantially free of PGMs other than Pd, Pt, and Rh. As used herein, the term "substantially free" is intended to mean that no PGMs other than Pd, Pt, and Rh are intentionally added or used in the layer. Those skilled in the art will appreciate that PGM(s) other than Pd, Pt, and Rh may be present in trace amounts in the top layer as impurities.
[0017] The bottom layer in a layered catalyst article according to the present invention is free of PGMs other than Pd intentionally added or used in the layer, and trace amounts of PGM(s) other than Pd may be present in the bottom layer as impurities.
[0018] The trace amounts of impurity PGM(s) may originate from the raw materials for preparing the respective layers and / or from migration of the PGM(s) into the layers, which may occur during supporting, coating and / or calcining in the process of preparing the catalyst article.
[0019] As used herein, a "trace amount" of PGM(s) means 1% by weight or less, including 0.75% by weight or less, 0.5% by weight or less, 0.25% by weight or less, or 0.1% by weight or less, based on the total loading of PGMs in the layer.
[0020] As used herein, reference to a platinum group metal in "supported form" is intended to mean that the platinum group metal is supported on and / or in a support in the form of particles. Reference to platinum and rhodium components being "supported together" means that the two platinum group metals are supported on and / or in the same support particle, for example by simultaneous or sequential impregnation of the support particle with their respective precursors. It will be understood that when platinum and rhodium components are supported together, both platinum and rhodium may be present on and / or in a single particle of the support.
[0021] The term "support" refers to a material for receiving and supporting a catalytically active component, such as a platinum group metal(s), and optionally one or more other components, such as stabilizers, promoters, and binders. The support may be selected from refractory metal oxides, oxygen storage components, and combinations thereof.
[0022] Refractory metal oxides that are widely used as supports for platinum group metals in exhaust gas treatment catalyst articles are generally high surface area alumina-based materials, zirconia-based materials, or combinations thereof. In the context of the present invention, "alumina-based materials" refers to materials that include alumina as a base and, optionally, dopants. Similarly, "zirconia-based materials" refers to materials that include zirconia as a base and, optionally, dopants.
[0023] Suitable examples of alumina-based materials include, but are not limited to, alumina, e.g., mixtures of gamma and delta phases of alumina that also contain significant amounts of eta, kappa and theta phases, lanthana-doped alumina, baria-doped alumina, ceria-doped alumina, zirconia-doped alumina, ceria-zirconia-doped alumina, lanthana-zirconia-doped alumina, baria-lanthana-doped alumina, baria-lanthana-neodymium-doped alumina, and any combination thereof.
[0024] Suitable examples of zirconia-based materials include, but are not limited to, zirconia, alumina-doped zirconia, lanthana-doped zirconia, yttria-doped zirconia, neodymia-doped zirconia, praseodymia-doped zirconia, titania-doped zirconia, titania-lanthana-doped zirconia, lanthana-yttria-doped zirconia, and any combination thereof.
[0025] For example, the refractory metal oxide is selected from alumina, lanthana doped alumina, lanthana-zirconia doped alumina, ceria doped alumina, zirconia doped alumina, ceria-zirconia doped alumina, zirconia, alumina doped zirconia, lanthana doped zirconia, lanthana-yttria doped zirconia, and any combination thereof.
[0026] Generally, the amount of refractory metal oxide, if used, is from 10 to 90 weight percent based on the total weight of the bottom or top layer.
[0027] Oxygen storage component (OSC) refers to a material that has multiple valence states and can actively react with oxidizing agents such as oxygen or nitrogen oxides under oxidizing conditions, or can react with reducing agents such as carbon monoxide (CO) or hydrogen under reducing conditions. Typically, OSCs include one or more reducible rare earth metal oxides, such as ceria. OSCs can also include one or more of lanthana, praseodymia, neodymia, europia, samaria, ytterbia, yttria, zirconia, and hafnia to form composite oxides with ceria. Preferably, the oxygen storage component is selected from ceria-zirconia composite oxides and rare earth stabilized ceria-zirconia composite oxides.
[0028] Generally, the amount of oxygen storage component, if used, is 20 to 80 weight percent based on the total weight of the bottom or top layer.
[0029] In the context of the present invention, there is no particular limitation on the support of the palladium component in the top layer and the bottom layer. The palladium component may be supported on a refractory metal oxide, an oxygen storage component, or any combination thereof. In some embodiments, the palladium component may be supported on one or more supports selected from a refractory metal oxide selected from an alumina-based material and a zirconia-based material, and an oxygen storage component.
[0030] Preferably, the palladium component in the top layer may be supported on one or more supports selected from alumina, lanthana-doped alumina, baria-doped alumina, ceria-doped alumina, zirconia-doped alumina, ceria-zirconia-doped alumina, lanthana-zirconia-doped alumina, baria-lanthana-doped alumina, baria-lanthana-neodymia-doped alumina, zirconia, lanthana-doped zirconia, yttria-doped zirconia, neodymia-doped zirconia, praseodymia-doped zirconia, titania-doped zirconia, titania-lanthana-doped zirconia, lanthana-yttria-doped zirconia, ceria, ceria-zirconia composite oxide, and rare earth-stabilized ceria-zirconia composite oxide, more preferably, on one or more supports selected from alumina, ceria-zirconia composite oxide, and rare earth-stabilized ceria-zirconia composite oxide.
[0031] Additionally or alternatively, preferably, the palladium component in the bottom layer may be supported on one or more supports selected from alumina, lanthana-doped alumina, baria-doped alumina, ceria-doped alumina, zirconia-doped alumina, ceria-zirconia-doped alumina, lanthana-zirconia-doped alumina, baria-lanthana-doped alumina, baria-lanthana-neodymia-doped alumina, ceria, ceria-zirconia composite oxide, and rare earth stabilized ceria-zirconia composite oxide, more preferably, on one or more supports selected from alumina, ceria-zirconia composite oxide, and rare earth stabilized ceria-zirconia composite oxide.
[0032] It is to be understood that the support for the palladium component in the top layer and the support for the palladium component in the bottom layer can be selected independently of each other, i.e., the support for the palladium component in the top layer can be the same as or different from the support for the palladium component in the bottom layer.
[0033] In the context of the present invention, it is preferred that at least a portion of the platinum component and at least a portion of the rhodium component in the top layer are co-supported on one or more supports other than alumina.
[0034] In some embodiments, at least a portion of the platinum component and at least a portion of the rhodium component may be supported together on one or more supports selected from ceria-doped alumina, zirconia-doped alumina, ceria-zirconia-doped alumina, lanthana-zirconia-doped alumina, baria-lanthana-doped alumina, baria-lanthana-neodymia-doped alumina, zirconia, lanthana-doped zirconia, yttria-doped zirconia, neodymia-doped zirconia, praseodymia-doped zirconia, titania-doped zirconia, titania-lanthana-doped zirconia, lanthana-yttria-doped zirconia, ceria, ceria-zirconia composite oxide, and rare earth-stabilized ceria-zirconia composite oxide. Preferably, at least a portion of the platinum component and at least a portion of the rhodium component may be supported on one or more supports selected from ceria-doped alumina, ceria-zirconia composite oxide, and rare earth-stabilized ceria-zirconia composite oxide.
[0035] If present, the support for the remaining portion of the platinum component, i.e., the individually supported portion, is not particularly limited. The support for the individually supported portion of the platinum component may be one or more selected from alumina-based materials and zirconia-based materials, and the oxygen storage components defined herein above for the palladium component.
[0036] When present, the support for the remaining portion of the rhodium component, i.e., the individually supported portion, is not particularly limited. In some embodiments, the support for the individually supported portion of the rhodium component may be one or more selected from alumina, ceria-doped alumina, zirconia-doped alumina, ceria-zirconia-doped alumina, lanthana-zirconia-doped alumina, baria-lanthana-doped alumina, zirconia, alumina-doped zirconia, lanthana-doped zirconia, yttria-doped zirconia, neodymia-doped zirconia, praseodymia-doped zirconia, titania-doped zirconia, titania-lanthana-doped zirconia, lanthana-yttria-doped zirconia, baria-lanthana-neodymia-doped alumina, ceria, ceria-zirconia composite oxide, and rare earth-stabilized ceria-zirconia composite oxide. Preferably, the rhodium component, when individually supported, may be supported on one or more supports selected from zirconia-doped alumina, ceria-zirconia-doped alumina, zirconia, alumina-doped zirconia, lanthana-doped zirconia, yttria-doped zirconia, neodymia-doped zirconia, praseodymia-doped zirconia, titania-doped zirconia, titania-lanthana-doped zirconia, lanthana-yttria-doped zirconia.
[0037] In some embodiments, the portion of the platinum component supported together with at least a portion of the rhodium component comprises at least 70%, such as at least 85%, of the total amount of platinum component, particularly all of the platinum component is supported on one or more supports together with at least a portion of the rhodium component in the top layer.
[0038] In some embodiments, all of the rhodium component is supported on one or more supports along with the platinum component. In other embodiments, a portion of the rhodium component is supported on one or more supports along with the platinum component, and the remaining portion of the rhodium component is supported individually on one or more supports. In the latter embodiments, the portion of the rhodium component supported along with the platinum component comprises at least 10%, at least 30%, at least 50% of the total rhodium component.
[0039] In some particular embodiments, the palladium component is loaded in the top and bottom layers in a ratio, calculated as elemental palladium, of greater than 1:1 to 10:1 or less, preferably in the range of 1.2:1 to 6:1, more preferably in the range of 1.5:1 to 4:1, and most preferably in the range of 2:1 to 4:1, for example 2.5:1 or 3:1.
[0040] The mass ratio of the palladium component to the platinum component in the layered catalyst article according to the invention, calculated as elemental palladium and platinum, can vary from 1:1 to 10:1. For example, the mass ratio of the palladium component to the platinum component in the layered catalyst article can be 2.0:1 or more, 2.1:1 or more, 2.3:1 or more. The mass ratio of the palladium component to the platinum component in the layered catalyst article can be 9:1 or less, 6:1 or less, 5:1 or less, or 4:1 or less. Thus, in some preferred embodiments, the palladium component and the platinum component can be included in the layered catalyst article according to the invention in a Pd / Pt mass ratio, calculated as elemental palladium and platinum, ranging from 2.0:1 to 9:1, 2.1:1 to 6:1, 2.3:1 to 5:1, or 2.3:1 to 4:1.
[0041] In the layered catalyst article according to the present invention, the mass ratio of the rhodium component to the palladium component, the mass ratio of the rhodium component to the platinum component, or the mass ratio of the rhodium component to the sum of the palladium component and the platinum component is not particularly limited. For example, in the layered catalyst article according to the present invention, the mass ratio of the rhodium component to the sum of the palladium component and the platinum component, calculated as each element, may be in the range of 2:3 to 1:200, 1:2 to 1:50, 1:3 to 1:20, or 1:3 to 1:10.
[0042] The mass ratio of the palladium component to the platinum component to the rhodium component in a layered catalyst article according to the present invention, calculated as each element, may be in the range of, for example, 1:1:1 to 10:1:0.2, 2:1:1 to 9:1:0.3, or 2:1:1 to 5:1:0.5.
[0043] Generally, platinum group metals, calculated as the sum of the individual elements, range from 1 to 250 g / ft 3 , 5~150g / ft 3 , or 5 to 100 g / ft 3 Additionally or alternatively, the palladium component may be loaded in the top layer in an amount of from 0.5 to 200 g / ft, calculated as elemental palladium. 3 , 1~150g / ft 3 , or 2 to 100 g / ft 3 may be carried on the bottom layer in an amount of
[0044] The total loading of the top layer is 1.5-4.0 g / in 3 Or 1.5~3g / in 3 and the total loading of the bottom layer is 0.75 to 3.0 g / in 3 Or 1.0~2.5g / in 3 may be also possible.
[0045] In some exemplary embodiments, the layered catalyst article according to the present invention comprises: a) a top layer comprising a palladium component, a platinum component and a rhodium component, the palladium component, the platinum component and the rhodium component being present in supported form, with all of the platinum component and at least a portion of the rhodium component together being supported on one or more supports selected from ceria-doped alumina, zirconia-doped alumina, ceria-zirconia-doped alumina, lanthana-zirconia-doped alumina, baria-lanthana-doped alumina, baria-lanthana-neodymia-doped alumina, zirconia, lanthana-doped zirconia, yttria-doped zirconia, neodymia-doped zirconia, praseodymia-doped zirconia, titania-doped zirconia, titania-lanthana-doped zirconia, lanthana-yttria-doped zirconia, ceria, ceria-zirconia composite oxides, and rare earth-stabilized ceria-zirconia composite oxides; b) a bottom layer comprising a palladium component in supported form as the sole platinum group metal component; and c) a substrate carrying the top layer and the bottom layer; Including, Here, the palladium component, calculated as elemental palladium, is supported in the top layer and the bottom layer at a ratio in the range of 1.2:1 to 6:1, preferably 1.5:1 to 4:1, and more preferably 2:1 to 4:1.
[0046] In a further exemplary embodiment, the layered catalyst article according to the present invention comprises: a) a top layer comprising a palladium component, a platinum component and a rhodium component, wherein all of the palladium component, the platinum component and the rhodium component are present in supported form, and the platinum component and at least a portion of the rhodium component are together supported on one or more supports selected from ceria-doped alumina, ceria-zirconia composite oxides, and rare earth stabilized ceria-zirconia composite oxides; b) a bottom layer comprising a palladium component in supported form as the sole platinum group metal component; and c) a substrate carrying the top layer and the bottom layer; Including, Here, the palladium component is supported in the top layer and the bottom layer at a ratio in the range of 1.5:1 to 4:1, preferably 2:1 to 4:1, calculated as palladium element.
[0047] Preferably, in each of the exemplary embodiments described above, the portion of the rhodium component co-supported with the platinum component comprises at least 30%, at least 50% of the total rhodium component.
[0048] More preferably, in each of the exemplary embodiments described above, the rhodium component, when individually supported, is supported on one or more supports selected from zirconia-doped alumina, ceria-zirconia-doped alumina, zirconia, alumina-doped zirconia, lanthana-doped zirconia, yttria-doped zirconia, neodymia-doped zirconia, praseodymia-doped zirconia, titania-doped zirconia, titania-lanthana-doped zirconia, lanthana-yttria-doped zirconia.
[0049] In some particular embodiments of the layered catalyst article according to the present invention, the bottom layer is applied onto a substrate and the top layer is applied onto the bottom layer without an intermediate layer.
[0050] The term "substrate" as used herein refers to a structure suitable for withstanding the conditions encountered in the exhaust gas stream of an internal combustion engine on which the catalyst composition is supported, typically in the form of a washcoat. The substrate is generally a ceramic or metal honeycomb structure having fine, parallel gas flow passages extending from one end of the structure to the other.
[0051] The term "washcoat" has its ordinary meaning in the art and refers to a thin, adherent coating of catalyst or other material applied to a substrate. Washcoats are generally formed by preparing a slurry containing particles at a certain solids content (e.g., 15-60% by weight) in a liquid vehicle, applying this to the substrate, drying, and calcining to provide the washcoat layer.
[0052] Metallic materials useful for constructing the substrate include heat-resistant metals and metal alloys such as titanium and stainless steel, and other alloys in which iron is a substantial or major component. Such alloys may contain one or more of nickel, chromium, and / or aluminum, and the total amount of these metals may advantageously comprise at least 15% by weight of the alloy, e.g., 10-25% by weight chromium, 3-8% by weight aluminum, and up to 20% by weight nickel. The alloy may contain small or trace amounts of one or more metals, such as manganese, copper, vanadium, titanium, etc. The surface of the metal substrate is oxidized at high temperatures, e.g., above 1000°C, to form an oxide layer on the substrate surface, thereby improving the corrosion resistance of the alloy and facilitating the adhesion of a washcoat layer to the metal surface.
[0053] Ceramic materials useful for constructing the substrate include any suitable refractory material, such as cordierite, mullite, cordierite-alumina, silicon nitride, zircon-mullite, spodumene, alumina-silica-magnesia, zircon silicate, sillimanite, magnesium silicate, zircon, petalite, alumina, and aluminosilicate.
[0054] In the context of the present invention, monolithic flow-through substrates are preferred, having a plurality of fine, parallel gas flow passages extending from the inlet face to the outlet face of the substrate, the passages being open to the flow of fluid therethrough. The passages, which are substantially straight from the fluid inlet to the fluid outlet, are defined by walls to which a catalytic material is applied as a washcoat, such that gas flowing through the passages contacts the catalytic material. The flow paths of the monolithic substrate are thin-walled channels and can be of any suitable cross-sectional shape and size, such as trapezoidal, rectangular, square, sinusoidal, hexagonal, elliptical, circular, etc. Such structures may contain from about 60 to about 900 or more gas inlet openings (i.e., cells) per square inch of cross section. For example, the substrate can have from about 400 to about 900, more usually from about 600 to about 750 cells per square inch ("cpsi"). The wall thickness of the flow-through substrates can vary, typically ranging from 2 mils to 0.1 inches. A typical flow-through substrate is a cordierite substrate having a cell density of 600 cpsi or 750 cpsi and a wall thickness of 2 mils.
[0055] It is also possible for the substrate to be a wall-flow substrate having a plurality of fine, parallel gas flow passages extending from the inlet of the substrate along the outlet face, with alternating passages being plugged at the opposite end. In this configuration, the gas flow must reach the outlet face through the porous walls of the wall-flow substrate. The wall-flow substrate may contain up to about 700 cells per square inch (cpsi), for example, about 100 to 400 cpsi, more typically about 200 to about 300 cpsi. The cross-sectional shape of the cells can be varied as described above. The flow paths of the monolith substrate are thin-walled channels and can be of any suitable cross-sectional shape and size, such as trapezoidal, rectangular, square, sinusoidal, hexagonal, elliptical, circular, etc. The wall thickness of the wall-flow substrate can vary, typically ranging from 2 mils to 0.1 inches.
[0056] Layered catalyst articles according to the present invention can be prepared conventionally, for example, by a process including depositing a bottom-coat slurry to obtain a bottom layer, followed by depositing a top-coat slurry to obtain a top layer.
[0057] Generally, the slurries comprise catalyst particles, a solvent (e.g., water), an optional binder, and optional auxiliary agents such as surfactants, pH adjusters, thickeners, etc. In particular, the bottom coat slurry comprises a palladium component in supported form as catalyst particles, and the top coat slurry comprises a palladium component in supported form, platinum and rhodium components supported together, and optionally individually supported platinum and / or rhodium components as catalyst particles. The supports for the PGMs are as described herein above.
[0058] These catalyst particles can be prepared by impregnating the precursors of the PGM(s), such as soluble salts and / or their complexes, into the respective supports by conventional techniques such as dry impregnation (also called incipient wetness impregnation or capillary impregnation) or wet impregnation, optionally followed by drying and / or calcination. Suitable precursors of the PGMs can be selected from ammine complex salts, hydroxyl salts, nitrates, carboxylates, ammonium salts, oxides and colloids of the PGMs. Non-limiting examples include palladium nitrate, tetraamminepalladium nitrate, rhodium nitrate, tetraammineplatinum acetate, platinum nitrate, tetraammineplatinum acetate, diethanolamine hexahydroxyplatinate ((HOCH2CH2NH3)2[Pt(OH)6]) and colloidal platinum.
[0059] The binder may be selected from alumina, boehmite, silica, zirconium acetate, colloidal zirconia, or zirconium hydroxide. When present, the binder is typically used in an amount of about 0.5 to about 5.0 weight percent of the total washcoat loading.
[0060] The slurry may have a solids content in the range of, for example, about 20-60% by weight, more particularly about 30-50% by weight. The slurry is often milled to reduce particle size. Typically, the slurry has a D of about 3.0 to about 40 microns, preferably about 10 to about 30 microns, more preferably less than about 20 microns, after milling, as measured by a laser diffraction particle size distribution analyzer. 90 It has a particle size.
[0061] Deposition of the slurry onto the substrate or undercoat may be performed by any technique known in the art. For example, the substrate may be dipped into the slurry one or more times or otherwise coated with the slurry to a desired length, then dried at an elevated temperature (e.g., 100-150°C) for a period of time (e.g., 10 minutes to 3 hours), and calcined at a higher temperature (e.g., 400-700°C) for typically about 10 minutes to about 3 hours. The washcoat loading after calcination can be determined by calculating the mass difference between the coated and uncoated substrate. As will be apparent to one skilled in the art, the washcoat loading can be altered by modifying the slurry rheology. Additionally, the deposition process, including coating, drying, and calcining to produce a washcoat, can be repeated as necessary to form a layer of the desired loading level or thickness, i.e., multiple washcoats can be applied.
[0062] In some embodiments, the layered catalyst articles according to the invention may further comprise a functional layer applied by a "dry coating" method, in which one or more functional materials are applied via a gas phase carrier without the use of a liquid carrier. In these layered catalyst articles, the substrate is in particular a wall-flow substrate, and the functional layer is on the outermost side of the porous wall of the substrate.
[0063] According to another aspect of the present invention, there is provided an exhaust gas treatment system comprising a layered catalyst article as described herein disposed downstream of an internal combustion engine, particularly a gasoline engine, which may be disposed in close proximity, downstream of close proximity, or both.
[0064] According to a further aspect of the present invention, there is provided a method of treating an exhaust gas stream comprising contacting the exhaust gas stream with a layered catalyst article or an exhaust gas treatment system described herein.
[0065] "Exhaust gas stream," "exhaust gas," and like terms refer to any engine exhaust gas that may contain solid or liquid particulate matter.
[0066] The layered catalyst articles according to the present invention are particularly useful for the reduction of hydrocarbons, carbon monoxide and nitrogen oxides in the exhaust gas stream from internal combustion engines, especially gasoline engines.
[0067] Embodiment Various embodiments are listed below, and it is to be understood that the embodiments listed below can be combined with all aspects and other embodiments in accordance with the scope of the present invention.
[0068] 1. A layered catalyst article, particularly useful for three-way conversion, comprising: a) a top layer comprising a palladium (Pd), platinum (Pt) and rhodium (Rh) component, the palladium, platinum and rhodium components being present in supported form, with at least a portion of the platinum and at least a portion of the rhodium components being co-supported on one or more supports; b) a bottom layer comprising a palladium component in supported form as the sole platinum group metal component; and c) a substrate carrying the top layer and the bottom layer; Including, A layered catalyst article wherein the palladium component, calculated as elemental palladium, is supported in said top layer and said bottom layer in a ratio of greater than 1:1.
[0069] 2. The layered catalyst article of embodiment 1, wherein the top layer is substantially free of PGMs other than Pd, Pt, and Rh.
[0070] 3. The layered catalyst article of embodiment 1 or 2, wherein at least a portion of the platinum component and at least a portion of the rhodium component in the top layer are co-supported on one or more supports other than alumina.
[0071] 4. The layered catalyst article of any one of claims 1 to 3, wherein at least a portion of the platinum component and at least a portion of the rhodium component are supported together on one or more supports selected from ceria-doped alumina, zirconia-doped alumina, ceria-zirconia-doped alumina, lanthana-zirconia-doped alumina, baria-lanthana-doped alumina, baria-lanthana-neodymia-doped alumina, zirconia, lanthana-doped zirconia, yttria-doped zirconia, neodymia-doped zirconia, praseodymia-doped zirconia, titania-doped zirconia, titania-lanthana-doped zirconia, lanthana-yttria-doped zirconia, ceria, ceria-zirconia composite oxides, and rare earth-stabilized ceria-zirconia composite oxides.
[0072] 5. The layered catalyst article of any one of the preceding claims, wherein at least a portion of the platinum component and at least a portion of the rhodium component are together supported on one or more supports selected from ceria-doped alumina, ceria-zirconia composite oxides, and rare earth stabilized ceria-zirconia composite oxides.
[0073] 6. The layered catalyst article of any one of the preceding claims, wherein at least 70%, preferably all, of the platinum component is supported on one or more supports together with at least a portion of the rhodium component in the top layer.
[0074] 7. The layered catalyst article of any one of the preceding claims, wherein at least 10%, at least 30%, or at least 50% of the rhodium component is supported on one or more supports along with the platinum component in the top layer.
[0075] 8. The layered catalyst article of any one of embodiments 1 to 7, wherein the palladium component is supported in the top layer and the bottom layer in a ratio, calculated as elemental palladium, of greater than 1:1 to 10:1 or less, preferably in the range of 1.2:1 to 6:1, more preferably in the range of 1.5:1 to 4:1, and most preferably in the range of 2:1 to 4:1, such as 2.5:1 or 3:1.
[0076] 9.a) a top layer comprising a palladium component, a platinum component and a rhodium component, said palladium component, platinum component and rhodium component being present in supported form, with all of said platinum component and at least a portion of said rhodium component together being supported on one or more supports selected from ceria-doped alumina, zirconia-doped alumina, ceria-zirconia-doped alumina, lanthana-zirconia-doped alumina, baria-lanthana-doped alumina, baria-lanthana-neodymia-doped alumina, zirconia, lanthana-doped zirconia, yttria-doped zirconia, neodymia-doped zirconia, praseodymia-doped zirconia, titania-doped zirconia, titania-lanthana-doped zirconia, lanthana-yttria-doped zirconia, ceria, ceria-zirconia composite oxides and rare earth stabilized ceria-zirconia composite oxides; b) a bottom layer comprising a palladium component in supported form as the sole platinum group metal component; and c) a substrate carrying the top layer and the bottom layer; Including, 9. The layered catalyst article of any one of the preceding claims, wherein the palladium component is supported in the top layer and the bottom layer in a ratio, calculated as elemental palladium, ranging from 1.2:1 to 6:1, preferably from 1.5:1 to 4:1, more preferably from 2:1 to 4:1.
[0077] 10.a) a top layer comprising a palladium component, a platinum component and a rhodium component, wherein the palladium component, all of the platinum component and the rhodium component are present in supported form, and all of the platinum component and at least a portion of the rhodium component are together supported on one or more supports selected from ceria-doped alumina, ceria-zirconia composite oxides, and rare earth stabilized ceria-zirconia composite oxides; b) a bottom layer comprising a palladium component in supported form as the sole platinum group metal component; and c) a substrate carrying the top layer and the bottom layer; Including, 10. The layered catalyst article of any one of the preceding claims, wherein the palladium component is supported in the top layer and the bottom layer in a ratio ranging from 1.5:1 to 4:1, preferably from 2:1 to 4:1, calculated as elemental palladium.
[0078] 11. The layered catalyst article of any one of the preceding claims, wherein the mass ratio of the palladium component to the platinum component present in the layered catalyst article, calculated as elemental palladium and elemental platinum, is in the range of 1:1 to 10:1, for example, 2.0:1 to 9:1, 2.1:1 to 6:1, or 2.3:1 to 5:1, or 2.3:1 to 4:1.
[0079] 12. The layered catalyst article of any one of the preceding claims, wherein the mass ratio of the rhodium component to the sum of the palladium component and the platinum component in the layered catalyst article, calculated as each element, is in the range of 2:3 to 1:200, 1:2 to 1:50, 1:3 to 1:20, or 1:3 to 1:10.
[0080] 13. The layered catalyst article of any one of embodiments 1 to 12, wherein the mass ratio of the palladium component to the platinum component to the rhodium component in the layered catalyst article, calculated as each element, is in the range of 1:1:1 to 10:1:0.2, 2:1:1 to 9:1:0.3, or 2:1:1 to 5:1:0.5.
[0081] 14. Platinum group metals, calculated as the sum of each element, are between 1 and 250 g / ft 3 , 5~150g / ft 3 , or 5 to 100 g / ft 3 and / or the palladium component is supported on the top layer in an amount of 0.5 to 200 g / ft, calculated as elemental palladium. 3 , 1~150g / ft 3 , or 2 to 100 g / ft 3 14. The layered catalyst article of any one of the preceding claims, wherein the bottom layer is supported in an amount of
[0082] 15. The layered catalyst article of any one of the preceding claims, wherein the bottom layer is applied onto the substrate and the top layer is applied onto the bottom layer without an intermediate layer.
[0083] 16. The layered catalyst article of any one of the preceding claims, wherein the substrate is a flow-through substrate or a wall-flow substrate.
[0084] 17. A method of using the layered catalyst article of any one of embodiments 1 to 16 for the reduction of hydrocarbons, carbon monoxide, and nitrogen oxides in an exhaust gas stream.
[0085] 18. An exhaust gas treatment system comprising a layered catalyst article according to any one of embodiments 1 to 16 arranged downstream of an internal combustion engine, in particular a gasoline engine.
[0086] 19. The exhaust gas treatment system of embodiment 18, wherein the layered catalyst article is positioned downstream of the internal combustion engine in a close-by position, an underfloor position, or both.
[0087] 20. The exhaust gas treatment system of embodiment 18 or 19, wherein the layered catalyst article is followed directly or indirectly by a four-way catalytic converter.
[0088] 21. A method for treating an exhaust gas stream, comprising contacting the exhaust gas stream with the layered catalyst article of any one of embodiments 1 to 16 or the exhaust gas treatment system of any one of embodiments 18 to 20.
[0089] 22. The method of embodiment 21, wherein the layered catalyst article is particularly useful for the reduction of hydrocarbons, carbon monoxide, and nitrogen oxides in exhaust gas streams from internal combustion engines, particularly gasoline engines. EXAMPLES
[0090] Aspects of the present invention will be more fully described by the following examples, which are provided to illustrate particular aspects of the invention and are not to be construed as limiting thereof.
[0091] Example 1: Layered bimetallic catalyst article (reference, BMC-1, Pt / Pd / Rh=0 / 50 / 10, g / ft 3 Preparation of A catalyst article was prepared that included a bottom coat with palladium (Pd) as the only PGM and a top coat with palladium (Pd) and rhodium (Rh) as PGMs, and a schematic diagram of this catalyst is shown in Figure 1A.
[0092] Bottom coat slurry: 18.1 grams of 20% aqueous palladium nitrate solution, 109 grams of alumina, and 822 grams of ceria-zirconia (50% zirconia) were mixed with water and then cooled to 50° C. 90 The mixture was ground to a particle size of less than 18 μm. The pH was adjusted to about 4.0 by the addition of acetic acid, and then 18 grams of alumina binder was added.
[0093] Topcoat Slurry: The first component was prepared by impregnating 45.29 grams of a 20% aqueous palladium nitrate solution into 240 grams of alumina and 335 grams of ceria-zirconia (50% zirconia) by incipient wetness impregnation. This step was followed by drying at 150° C. for 1 hour and then calcination at 500° C. for 2 hours to fix the PGM on the support. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0094] The second component was prepared by impregnating 22.65 grams of a 10% aqueous rhodium nitrate solution into 144 grams of zirconia and 241 grams of ceria-zirconia (70% zirconia) by incipient wetness impregnation. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0095] The two components in the form of a slurry were mixed together, the pH was adjusted to about 8.0 by the addition of barium hydroxide and nitric acid, and then 20 grams of alumina binder was added.
[0096] The bottom coat slurry was coated onto a 600 / 2 (cpsi / mil) flow-through ceramic substrate with a diameter of 132.1 mm and a length of 50 mm, dried at 150°C for 1 hour, and then calcined at 500°C for 2 hours. The washcoat loading was 1.5 g / in 3 The bottom coating had a Pd loading of 10 g / ft 3 The topcoat slurry was then applied and dried at 150°C for 1 hour, followed by calcination at 500°C for 2 hours. The washcoat loading was 2.5 g / in 3 The topcoat had a PGM loading of 40 g / ft 3 of Pd and 10g / ft 3 It consisted of Rh.
[0097] Example 2: Layered trimetallic catalyst article (reference, TMC-1, Pt / Pd / Rh=15 / 35 / 10, g / ft 3 Preparation of A catalyst article was prepared that included a bottom coat with palladium (Pd) as the only PGM and a top coat with palladium (Pd), platinum (Pt) and rhodium (Rh) as PGMs. A schematic diagram of this catalyst article is shown in Figure 1B. This catalyst article (TMC-1) represents a modification of the catalyst article (BMC-1) with a simple substitution of 30% of the Pd in the top coat with Pt.
[0098] Bottom coat slurry: 18.1 grams of 20% aqueous palladium nitrate solution, 109 grams of alumina, 822 grams of ceria-zirconia (50% zirconia) were mixed with water and then D 90 The mixture was ground to a particle size of less than 18 μm. The pH was adjusted to about 4.0 by the addition of acetic acid, and then 18 grams of alumina binder was added.
[0099] Topcoat Slurry: The first component was prepared by first impregnating 240 grams of alumina and 335 grams of ceria-zirconia (50% zirconia) with 20.34 grams of a 16% aqueous solution of hexahydroxyplatinic acid diethanolamine salt by incipient wetness impregnation, followed by 28.31 grams of a 20% aqueous solution of palladium nitrate. This step was followed by drying at 150° C. for 1 hour and then calcining at 500° C. for 2 hours to fix the PGM on the support. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0100] The second component was prepared by impregnating 22.65 grams of a 10% aqueous rhodium nitrate solution into 144 grams of zirconia and 241 grams of ceria-zirconia (70% zirconia) by incipient wetness impregnation. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0101] The two components in the form of a slurry were mixed together, the pH was adjusted to about 8.0 by the addition of barium hydroxide and nitric acid, and then 20 grams of alumina binder was added.
[0102] The bottom coat slurry was coated onto a 600 / 2 (cpsi / mil) flow-through ceramic substrate with a diameter of 132.1 mm and a length of 50 mm, dried at 150°C for 1 hour, and then calcined at 500°C for 2 hours. The washcoat loading was 1.5 g / in 3 The bottom coating had a Pd loading of 10 g / ft 3 The topcoat slurry was then applied and dried at 150°C for 1 hour, followed by calcination at 500°C for 2 hours. The washcoat loading was 2.5 g / in 3 The topcoat had a PGM loading of 15 g / ft 3 Pt, 25g / ft 3 of Pd and 10g / ft 3 It consisted of Rh.
[0103] Example 3: Layered trimetallic catalyst article (invention, TMC-2, Pt / Pd / Rh=15 / 35 / 10, g / ft 3 Preparation of A catalytic article was prepared that included a bottom coat with palladium (Pd) as the only PGM and a top coat with palladium (Pd), platinum (Pt) and rhodium (Rh) as PGMs. Platinum (Pt) and rhodium (Rh) were supported together in the top coat. A schematic diagram of this catalytic article is shown in FIG. 1C.
[0104] Bottom coat slurry: 18.1 grams of 20% aqueous palladium nitrate solution, 109 grams of alumina, 822 grams of ceria-zirconia (50% zirconia) were mixed with water and then D 90 The mixture was ground to a particle size of less than 18 μm. The pH was adjusted to about 4.0 by the addition of acetic acid, and then 18 grams of alumina binder was added.
[0105] Topcoat Slurry: The first component was prepared by impregnating 28.31 grams of a 20% aqueous palladium nitrate solution into 240 grams of alumina and 335 grams of ceria-zirconia (50% zirconia) by incipient wetness impregnation. This step was followed by drying at 150° C. for 1 hour and then calcination at 500° C. for 2 hours to fix the PGM on the support. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0106] The second component was prepared by first impregnating 144 grams of zirconia and 241 grams of ceria-zirconia (70% zirconia) with 20.34 grams of a 16% aqueous solution of hexahydroxyplatinic acid diethanolamine salt by incipient wetness impregnation, followed by impregnation with 22.65 grams of a 10% aqueous solution of rhodium nitrate. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0107] The two components in the form of a slurry were mixed together, the pH was adjusted to about 8.0 by the addition of barium hydroxide and nitric acid, and then 20 grams of alumina binder was added.
[0108] The bottom coat slurry was coated onto a 600 / 2 (cpsi / mil) flow-through ceramic substrate with a diameter of 132.1 mm and a length of 50 mm, dried at 150°C for 1 hour, and then calcined at 500°C for 2 hours. The washcoat loading was 1.5 g / in 3 The bottom coating had a Pd loading of 10 g / ft 3 The topcoat slurry was then applied and dried at 150°C for 1 hour, followed by calcination at 500°C for 2 hours. The washcoat loading was 2.5 g / in 3 The topcoat had a PGM loading of 15 g / ft 3 Pt, 25g / ft 3 of Pd and 10g / ft 3 It consisted of Rh.
[0109] Example 4: Layered trimetallic catalyst article (invention, TMC-3, Pt / Pd / Rh=15 / 35 / 4, g / ft 3 Preparation of A catalytic article was prepared that included a bottom coat with palladium (Pd) as the only PGM and a top coat with palladium (Pd), platinum (Pt) and rhodium (Rh) as PGMs, a schematic diagram of which is shown in Figure 2A.
[0110] Bottom coat slurry: 18.1 grams of 20% aqueous palladium nitrate solution, 109 grams of alumina, 822 grams of ceria-zirconia (50% zirconia) were mixed with water and then D 90 The mixture was ground to a particle size of less than 18 μm. The pH was adjusted to about 4.0 by the addition of acetic acid, and then 18 grams of alumina binder was added.
[0111] Topcoat Slurry: The first component was prepared by impregnating 28.31 grams of a 20% aqueous palladium nitrate solution into 240 grams of alumina and 335 grams of ceria-zirconia (50% zirconia) by incipient wetness impregnation. This step was followed by drying at 150° C. for 1 hour and then calcination at 500° C. for 2 hours to fix the PGM on the support. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0112] The second component was prepared by first impregnating 385 grams of ceria-zirconia (75% zirconia) with 20.34 grams of a 16% aqueous solution of hexahydroxyplatinic acid diethanolamine salt, followed by 9.06 grams of a 10% aqueous solution of rhodium nitrate, by incipient wetness impregnation. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0113] The two components in the form of a slurry were mixed together, the pH was adjusted to about 8.0 by the addition of barium hydroxide and nitric acid, and then 20 grams of alumina binder was added.
[0114] The bottom coat slurry was coated onto a 750 / 2 (cpsi / mil) flow-through ceramic substrate with a diameter of 25.4 mm and a length of 76.2 mm, dried at 150°C for 1 hour, and then calcined at 500°C for 2 hours. The washcoat loading was 1.5 g / in 3 The bottom coating had a Pd loading of 10 g / ft 3 The topcoat slurry was then applied and dried at 150°C for 1 hour, followed by calcination at 500°C for 2 hours. The washcoat loading was 2.5 g / in 3 The topcoat had a PGM loading of 15 g / ft 3 Pt, 25g / ft 3 of Pd and 4g / ft 3 It consisted of Rh.
[0115] Example 5: Layered trimetallic catalyst article (Comparative, TMC-4, Pt / Pd / Rh=15 / 35 / 4, g / ft 3Preparation of A catalytic article was prepared that included a bottom coat with palladium (Pd) as the only PGM and a top coat with palladium (Pd), platinum (Pt) and rhodium (Rh) as PGMs, a schematic diagram of which is shown in FIG. 2B.
[0116] Bottom coat slurry: 28.31 grams of 20% aqueous palladium nitrate solution, 109 grams of alumina, 822 grams of ceria-zirconia (50% zirconia) were mixed with water and then D 90 The mixture was ground to a particle size of less than 18 μm. The pH was adjusted to about 4.0 by the addition of acetic acid, and then 18 grams of alumina binder was added.
[0117] Topcoat Slurry: The first component was prepared by impregnating 18.10 grams of a 20% aqueous palladium nitrate solution into 240 grams of alumina and 335 grams of ceria-zirconia (50% zirconia) by incipient wetness impregnation. This step was followed by drying at 150° C. for 1 hour and then calcination at 500° C. for 2 hours to fix the PGM on the support. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0118] The second component was prepared by first impregnating 385 grams of ceria-zirconia (75% zirconia) with 20.34 grams of a 16% aqueous solution of hexahydroxyplatinic acid diethanolamine salt, followed by 9.06 grams of a 10% aqueous solution of rhodium nitrate, by incipient wetness impregnation. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0119] The two components in the form of a slurry were mixed together, the pH was adjusted to about 8.0 by the addition of barium hydroxide and nitric acid, and then 20 grams of alumina binder was added.
[0120] The bottom coat slurry was coated onto a 750 / 2 (cpsi / mil) flow-through ceramic substrate with a diameter of 25.4 mm and a length of 76.2 mm, dried at 150°C for 1 hour, and then calcined at 500°C for 2 hours. The washcoat loading was 1.5 g / in 3 The bottom coating had a Pd loading of 10 g / ft 3 The topcoat slurry was then applied and dried at 150°C for 1 hour, followed by calcination at 500°C for 2 hours. The washcoat loading was 2.5 g / in 3 The topcoat had a PGM loading of 15 g / ft 3 Pt, 10g / ft 3 of Pd and 4g / ft 3 It consisted of Rh.
[0121] Example 6: Layered trimetallic catalyst article (Comparative, TMC-5, Pt / Pd / Rh=15 / 35 / 4, g / ft 3 Preparation of A catalytic article was prepared that included a bottom coat with palladium (Pd), platinum (Pt) and rhodium (Rh) as PGMs and a top coat with palladium (Pd) as the only PGM, and a schematic diagram of the catalytic article is shown in Figure 2C.
[0122] Bottom Coat Slurry: The first component was prepared by impregnating 28.31 grams of a 20% aqueous palladium nitrate solution into 240 grams of alumina and 335 grams of ceria-zirconia (50% zirconia) by incipient wetness impregnation. This step was followed by drying at 150° C. for 1 hour and then calcination at 500° C. for 2 hours to fix the PGM on the support. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0123] The second component was prepared by first impregnating 385 grams of ceria-zirconia (75% zirconia) with 20.34 grams of a 16% aqueous solution of hexahydroxyplatinic acid diethanolamine salt, followed by 9.06 grams of a 10% aqueous solution of rhodium nitrate, by incipient wetness impregnation. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0124] The two components in the form of a slurry were mixed together, the pH was adjusted to about 8.0 by the addition of barium hydroxide and nitric acid, and then 20 grams of alumina binder was added.
[0125] Topcoat Slurry: 18.1 grams of a 20% aqueous solution of palladium nitrate, 109 grams of alumina, and 822 grams of ceria-zirconia (50% zirconia) were mixed with water and then cooled to 37°C. 90 The mixture was ground to a particle size of less than 18 μm. The pH was adjusted to about 4.0 by the addition of acetic acid, and then 18 grams of alumina binder was added.
[0126] The bottom coat slurry was coated onto a 750 / 2 (cpsi / mil) flow-through ceramic substrate with a diameter of 25.4 mm and a length of 76.2 mm, dried at 150° C. for 1 hour, and then calcined at 500° C. for 2 hours. The washcoat loading was 2.5 g / in 3 The bottom coat had a PGM loading of 15 g / ft 3 Pt, 25g / ft 3 of Pd and 4g / ft 3 The topcoat slurry was then applied and dried at 150 °C for 1 hour, then calcined at 500 °C for 2 hours. The washcoat loading was 1.5 g / in 3 The top coat had a Pd loading of 10 g / ft 3 It was.
[0127] Example 7: Layered trimetallic catalyst article (Comparative, TMC-6, Pt / Pd / Rh=15 / 35 / 4, g / ft 3 Preparation of A catalytic article was prepared that included a bottom coat with palladium (Pd) as the only PGM and a top coat with palladium (Pd), platinum (Pt) and rhodium (Rh) as PGMs, a schematic of which is shown in Figure 2D.
[0128] Bottom coat slurry: 18.1 grams of 20% aqueous palladium nitrate solution, 109 grams of alumina, 822 grams of ceria-zirconia (50% zirconia) were mixed with water and then D 90 The mixture was ground to a particle size of less than 18 μm. The pH was adjusted to about 4.0 by the addition of acetic acid, and then 18 grams of alumina binder was added.
[0129] Topcoat Slurry: The first component was prepared by impregnating 28.31 grams of a 20% aqueous palladium nitrate solution into 240 grams of alumina and 335 grams of ceria-zirconia (50% zirconia) by incipient wetness impregnation. This step was followed by drying at 150° C. for 1 hour and then calcination at 500° C. for 2 hours to fix the PGM on the support. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0130] The second component was prepared by first impregnating 385 grams of alumina with 20.34 grams of a 16% aqueous solution of hexahydroxyplatinic acid diethanolamine salt, followed by 9.06 grams of a 10% aqueous solution of Rh nitrate, via incipient wetness impregnation. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0131] The two components in the form of a slurry were mixed together, the pH was adjusted to about 8.0 by the addition of barium hydroxide and nitric acid, and then 20 grams of alumina binder was added.
[0132] The bottom coat slurry was coated onto a 750 / 2 (cpsi / mil) flow-through ceramic substrate with a diameter of 25.4 mm and a length of 76.2 mm, dried at 150°C for 1 hour, and then calcined at 500°C for 2 hours. The washcoat loading was 1.5 g / in 3 The bottom coating had a Pd loading of 10 g / ft 3 The topcoat slurry was then applied and dried at 150°C for 1 hour, followed by calcination at 500°C for 2 hours. The washcoat loading was 2.5 g / in 3 The topcoat had a PGM loading of 15 g / ft 3 Pt, 25g / ft 3 of Pd and 4g / ft 3 It consisted of Rh.
[0133] Example 8: Layered trimetallic catalyst article (invention, TMC-7, Pt / Pd / Rh=15 / 35 / 4, g / ft 3 Preparation of A catalytic article was prepared that included a bottom coat with palladium (Pd) as the only PGM and a top coat with palladium (Pd), platinum (Pt) and rhodium (Rh) as PGMs, a schematic diagram of which is shown in Figure 3A.
[0134] Bottom coat slurry: 18.1 grams of 20% aqueous palladium nitrate solution, 109 grams of alumina, 822 grams of ceria-zirconia (50% zirconia) were mixed with water and then D 90 The mixture was ground to a particle size of less than 18 μm. The pH was adjusted to about 4.0 by the addition of acetic acid, and then 18 grams of alumina binder was added.
[0135] Topcoat Slurry: The first component was prepared by impregnating 28.31 grams of a 20% aqueous palladium nitrate solution into 240 grams of alumina and 335 grams of ceria-zirconia (50% zirconia) by incipient wetness impregnation. This step was followed by drying at 150° C. for 1 hour and then calcination at 500° C. for 2 hours to fix the PGM on the support. The product was mixed with water and then D90 The powder was ground to a size of less than 18 μm.
[0136] The second component was prepared by first impregnating 385 grams of ceria-alumina (90% alumina) with 20.34 grams of a 16% aqueous solution of hexahydroxyplatinic acid diethanolamine salt, followed by 9.06 grams of a 10% aqueous solution of rhodium nitrate, by incipient wetness impregnation. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0137] The two components in the form of a slurry were mixed together, the pH was adjusted to about 8.0 by the addition of barium hydroxide and nitric acid, and then 20 grams of alumina binder was added.
[0138] The bottom coat slurry was coated onto a 750 / 2 (cpsi / mil) flow-through ceramic substrate with a diameter of 25.4 mm and a length of 76.2 mm, dried at 150°C for 1 hour, and then calcined at 500°C for 2 hours. The washcoat loading was 1.5 g / in 3 The bottom coating had a Pd loading of 10 g / ft 3 The topcoat slurry was then applied and dried at 150°C for 1 hour, followed by calcination at 500°C for 2 hours. The washcoat loading was 2.5 g / in 3 The topcoat had a PGM loading of 15 g / ft 3 Pt, 25g / ft 3 of Pd and 4g / ft 3 It consisted of Rh.
[0139] Example 9: Layered trimetallic catalyst article (Comparative, TMC-8, Pt / Pd / Rh=15 / 35 / 4, g / ft 3 Preparation of A catalytic article was prepared that included a bottom coat with palladium (Pd) as the only PGM and a top coat with palladium (Pd), platinum (Pt) and rhodium (Rh) as PGMs, a schematic diagram of which is shown in Figure 3B.
[0140] Bottom coat slurry: 18.1 grams of 20% aqueous palladium nitrate solution, 109 grams of alumina, 822 grams of ceria-zirconia (50% zirconia) were mixed with water and then D 90 The mixture was ground to a particle size of less than 18 μm. The pH was adjusted to about 4.0 by the addition of acetic acid, and then 18 grams of alumina binder was added.
[0141] Topcoat Slurry: The first component was prepared by impregnating 28.31 grams of a 20% aqueous palladium nitrate solution into 240 grams of alumina and 335 grams of ceria-zirconia (50% zirconia) by incipient wetness impregnation. This step was followed by drying at 150° C. for 1 hour and then calcination at 500° C. for 2 hours to fix the PGM on the support. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0142] The second component was prepared by impregnating 20.34 grams of a 16% aqueous solution of hexahydroxyplatinic acid diethanolamine salt into 257 grams of ceria-alumina (90% alumina) by incipient wetness impregnation. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0143] The third component was prepared by first impregnating 9.06 grams of a 10% aqueous rhodium nitrate solution into 128 grams of ceria-alumina (90% alumina) by incipient wetness impregnation. The product was mixed with water and then 90 The powder was ground to a size of less than 18 μm.
[0144] The three components in slurry form were mixed together, the pH was adjusted to about 8.0 by the addition of barium hydroxide and nitric acid, and then 20 grams of alumina binder was added.
[0145] The bottom coat slurry was coated onto a 750 / 2 (cpsi / mil) flow-through ceramic substrate with a diameter of 25.4 mm and a length of 76.2 mm, dried at 150°C for 1 hour, and then calcined at 500°C for 2 hours. The washcoat loading was 1.5 g / in 3 The bottom coating had a Pd loading of 10 g / ft 3 The topcoat slurry was then applied and dried at 150°C for 1 hour, followed by calcination at 500°C for 2 hours. The washcoat loading was 2.5 g / in 3 The topcoat had a PGM loading of 15 g / ft 3 Pt, 25g / ft 3 of Pd and 4g / ft 3 It consisted of Rh.
[0146] Example 10: Layered trimetallic catalyst article (Comparative, TMC-9, Pt / Pd / Rh=15 / 35 / 4, g / ft 3 Preparation of A catalytic article was prepared that included a bottom coat with palladium (Pd) as the only PGM and a top coat with palladium (Pd), platinum (Pt) and rhodium (Rh) as PGMs, and a schematic diagram of the catalytic article is shown in FIG.
[0147] Bottom Coat Slurry: 18.1 grams of a 20% aqueous solution of palladium nitrate, 109 grams of alumina, and 822 grams of ceria-zirconia (50% zirconia) were mixed with water and then cooled to 37°C. 90 The mixture was ground to a particle size of less than 18 μm. The pH was adjusted to about 4.0 by the addition of acetic acid, and then 18 grams of alumina binder was added.
[0148] Topcoat Slurry: The first component was prepared by impregnating 28.31 grams of a 20% aqueous palladium nitrate solution into 240 grams of alumina and 335 grams of ceria-zirconia (50% zirconia) by incipient wetness impregnation. This step was followed by drying at 150° C. for 1 hour and then calcination at 500° C. for 2 hours to fix the PGM on the support. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0149] The second component was prepared by impregnating 20.34 grams of a 16% aqueous solution of hexahydroxyplatinic acid diethanolamine salt into 257 grams of ceria-zirconia (75% zirconia) by incipient wetness impregnation. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0150] The third component was prepared by first impregnating 9.06 grams of a 10% aqueous rhodium nitrate solution into 128 grams of ceria-zirconia (75% zirconia) by incipient wetness impregnation. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0151] The three components in slurry form were mixed together, the pH was adjusted to about 8.0 by the addition of barium hydroxide and nitric acid, and then 20 grams of alumina binder was added.
[0152] The bottom coat slurry was coated onto a 750 / 2 (cpsi / mil) flow-through ceramic substrate with a diameter of 25.4 mm and a length of 76.2 mm, dried at 150°C for 1 hour, and then calcined at 500°C for 2 hours. The washcoat loading was 1.5 g / in 3 The bottom coating had a Pd loading of 10 g / ft 3 The topcoat slurry was then applied and dried at 150°C for 1 hour, followed by calcination at 500°C for 2 hours. The washcoat loading was 2.5 g / in 3 The topcoat had a PGM loading of 15 g / ft 3 Pt, 25g / ft 3of Pd and 4g / ft 3 It consisted of Rh.
[0153] Example 11: Layered trimetallic catalyst article (invention, TMC-10, Pt / Pd / Rh=13 / 35 / 6, g / ft 3 Preparation of A catalytic article was prepared that included a bottom coat with palladium (Pd) as the only PGM and a top coat with palladium (Pd), platinum (Pt) and rhodium (Rh) as PGMs, and a schematic diagram of the catalytic article is shown in FIG.
[0154] Bottom Coat Slurry: 18.1 grams of a 20% aqueous solution of palladium nitrate, 109 grams of alumina, and 822 grams of ceria-zirconia (50% zirconia) were mixed with water and then cooled to 37°C. 90 The mixture was ground to a particle size of less than 18 μm. The pH was adjusted to about 4.0 by the addition of acetic acid, and then 18 grams of alumina binder was added.
[0155] Topcoat Slurry: The first component was prepared by impregnating 28.31 grams of a 20% aqueous palladium nitrate solution into 240 grams of alumina and 335 grams of ceria-zirconia (50% zirconia) by incipient wetness impregnation. This step was followed by drying at 150° C. for 1 hour and then calcination at 500° C. for 2 hours to fix the PGM on the support. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0156] The second component was prepared by first impregnating 257 grams of ceria-alumina (90% alumina) with 17.63 grams of a 16% aqueous solution of hexahydroxyplatinic acid diethanolamine salt, followed by 4.53 grams of a 10% aqueous solution of rhodium nitrate, by incipient wetness impregnation. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0157] The third component was prepared by first impregnating 9.06 grams of a 10% aqueous rhodium nitrate solution into 128 grams of zirconia by incipient wetness impregnation. The product was mixed with water and then 90 The powder was ground to a size of less than 18 μm.
[0158] The three components in slurry form were mixed together, the pH was adjusted to about 8.0 by the addition of barium hydroxide and nitric acid, and then 20 grams of alumina binder was added.
[0159] The bottom coat slurry was coated onto a 750 / 2 (cpsi / mil) flow-through ceramic substrate with a diameter of 25.4 mm and a length of 76.2 mm, dried at 150°C for 1 hour, and then calcined at 500°C for 2 hours. The washcoat loading was 1.5 g / in 3 The bottom coating had a Pd loading of 10 g / ft 3 The topcoat slurry was then applied and dried at 150°C for 1 hour, followed by calcination at 500°C for 2 hours. The washcoat loading was 2.5 g / in 3 The topcoat had a PGM loading of 13 g / ft 3 Pt, 25g / ft 3 of Pd and 6g / ft 3 It consisted of Rh.
[0160] Example 12: Layered trimetallic catalyst article (invention, TMC-11, Pt / Pd / Rh=13 / 35 / 6, g / ft 3 Preparation of A catalytic article was prepared that included a bottom coat with palladium (Pd) as the only PGM and a top coat with palladium (Pd), platinum (Pt) and rhodium (Rh) as PGMs, a schematic of which is shown in FIG.
[0161] Bottom Coat Slurry: 18.1 grams of a 20% aqueous solution of palladium nitrate, 109 grams of alumina, and 822 grams of ceria-zirconia (50% zirconia) were mixed with water and then cooled to 37°C. 90The mixture was ground to a particle size of less than 18 μm. The pH was adjusted to about 4.0 by the addition of acetic acid, and then 18 grams of alumina binder was added.
[0162] Topcoat Slurry: The first component was prepared by impregnating 28.31 grams of a 20% aqueous palladium nitrate solution into 240 grams of alumina and 335 grams of ceria-zirconia (50% zirconia) by incipient wetness impregnation. This step was followed by drying at 150° C. for 1 hour and then calcination at 500° C. for 2 hours to fix the PGM on the support. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0163] The second component was prepared by first impregnating 257 grams of ceria-zirconia (75% zirconia) with 17.63 grams of a 16% aqueous solution of hexahydroxyplatinic acid diethanolamine salt, followed by 4.53 grams of a 10% aqueous solution of rhodium nitrate, by incipient wetness impregnation. The product was mixed with water and then D 90 The powder was ground to a size of less than 18 μm.
[0164] The third component was prepared by first impregnating 9.06 grams of a 10% aqueous rhodium nitrate solution into 128 grams of zirconia by incipient wetness impregnation. The product was mixed with water and then 90 The powder was ground to a size of less than 18 μm.
[0165] The three components in slurry form were mixed together, the pH was adjusted to about 8.0 by the addition of barium hydroxide and nitric acid, and then 20 grams of alumina binder was added.
[0166] The bottom coat slurry was coated onto a 750 / 2 (cpsi / mil) flow-through ceramic substrate with a diameter of 25.4 mm and a length of 76.2 mm, dried at 150°C for 1 hour, and then calcined at 500°C for 2 hours. The washcoat loading was 1.5 g / in 3 The bottom coating had a Pd loading of 10 g / ft 3The topcoat slurry was then applied and dried at 150°C for 1 hour, followed by calcination at 500°C for 2 hours. The washcoat loading was 2.5 g / in 3 The topcoat had a PGM loading of 13 g / ft 3 Pt, 25g / ft 3 of Pd and 6g / ft 3 It consisted of Rh.
[0167] Example 13: Catalytic performance test The catalyst article samples summarized in Table 1 were aged under condition 1) or condition 2): 1) Exothermic aging on a GM 8.1L V8 engine with an inlet temperature of 875°C; 2) Aging at 1050 °C under alternating lean / rich atmosphere (lean: 3 vol.% O, 10 vol.% HO, remaining N; rich: 1 vol.% H, 3 vol.% CO, 10 vol.% HO, remaining N, alternating every 5 min).
[0168] [Table 1]
[0169] The aged samples were tested using the Worldwide Harmonized Emissions Test Cycle (WLTC) for passenger vehicles in accordance with China-6 "Type I" (GB 18352.6-2016). The performance of the test samples was evaluated by measuring tailpipe total hydrocarbon (THC), CO and NOx emissions from one test cycle according to China-6 "Type I": P1: 0 to 589 seconds slow step, P2: Medium speed step of 590 seconds to 1022 seconds, P3: High speed stage from 1023 seconds to 1477 seconds, P4: Ultra-fast stage from 1478 seconds to 1800 seconds.
[0170] Samples S1-S3 were tested on a Daimler 2.0L engine bench, while samples S4-S13 were tested on a bench reactor (Gasoline Vehicle Simulator-GVS) capable of simulating vehicle driving conditions under WLTC, including temperature, flow rate (velocity), and exhaust gas composition (e.g., CO, HC, NO, H2O, CO2).
[0171] Each sample was tested three times, and the average values are summarized in Tables 2 to 4 as the test results.
[0172] [Table 2]
[0173] [Table 3]
[0174] [Table 4]
[0175] It is understood that the composition of engine exhaust gas can vary depending on engine conditions, for example, engine operating hours and distances. Samples S1-S3 were tested under substantially the same engine conditions to ensure that the inlet exhaust gases of the test samples were of substantially the same composition, allowing comparison of the samples with respect to measured emissions. Also, the remaining samples in the same group shown in the table were tested under substantially the same GVS conditions.
[0176] As can be seen from the measured emissions, Reference Sample S2 exhibited about 17% higher THC, about 32% higher CO, and about 29% higher NOx emissions compared to Reference Sample S1. Comparing the test results of Samples S1 and S2, it was confirmed that the incorporation of Pt by simply replacing a portion of the Pd in the TWC catalyst, as is generally recognized in the art, leads to worse control of THC, CO, and NOx emissions. Surprisingly, contrary to the trend of worsening emissions when replacing Pd with Pt, Sample S3 of the present invention, having a catalyst composition and configuration according to the present invention, exhibited about 2% lower CO and about 8% lower NOx emissions compared to Reference Sample S1.
[0177] It is also found that the layered trimetallic catalyst article of the present invention can provide improved emission control as compared to various variations of layered trimetallic catalyst articles with respect to catalyst composition and configuration.
[0178] Comparative sample S5, a variation of inventive sample S4 obtained by swapping the Pd loadings of the bottom and top coats, exhibited approximately 10% higher THC, approximately 2% higher CO, and approximately 15% higher NOx emissions compared to sample S4.
[0179] Comparative sample S6, a variation of inventive sample S4 obtained by swapping the bottom and top coats, exhibited approximately 4% higher THC, approximately 3% higher CO, and approximately 3% higher NOx emissions compared to sample S4.
[0180] Comparative sample S7, which is a modification of sample S4 of the present invention in which the support carrying both Pt and Rh was replaced with alumina, exhibited approximately 8% higher THC, approximately 18% higher CO, and approximately 25% higher NOx emissions than sample S4.
[0181] Comparative sample S9, which is a variation of sample S8 of the present invention obtained by separately supporting Pt and Rh, showed about 4% higher THC, about 4% higher CO, and about 10% higher NOx emissions compared to sample S8.
[0182] Comparative sample S11, which is a variation of sample S10 of the present invention obtained by separately supporting Pt and Rh, exhibited about 6% higher THC, about 3% higher CO, and about 6% higher NOx emissions than sample S10.
[0183] Although the present invention has been described herein with reference to particular embodiments, it should be understood that these embodiments are merely illustrative of the principles and applications of the present invention. It will be apparent to those skilled in the art that various modifications and variations can be made to the method and apparatus of the present invention without departing from the spirit and scope of the invention. Therefore, it is intended that the present invention cover such modifications and variations as come within the scope of the appended claims and their equivalents.
Claims
1. a) a top layer comprising a palladium (Pd), platinum (Pt) and rhodium (Rh) component, the palladium, platinum and rhodium components being present in supported form, with at least a portion of the platinum and at least a portion of the rhodium components being co-supported on one or more supports; b) a bottom layer comprising a palladium component in supported form as the sole platinum group metal component; and c) a substrate carrying the top layer and the bottom layer; 1. A layered catalyst article comprising: A layered catalyst article wherein the palladium component, calculated as elemental palladium, is supported in said top layer and said bottom layer in a ratio of greater than 1:
1.
2. 10. The layered catalyst article of claim 1, wherein the top layer is substantially free of PGMs other than Pd, Pt and Rh.
3. 3. The layered catalyst article of claim 1 or 2, wherein at least a portion of said platinum component and at least a portion of said rhodium component in said top layer are co-supported on one or more supports other than alumina.
4. 3. The layered catalyst article of claim 1 or 2, wherein at least a portion of the platinum component and at least a portion of the rhodium component are supported together on one or more supports selected from ceria-doped alumina, zirconia-doped alumina, ceria-zirconia-doped alumina, lanthana-zirconia-doped alumina, baria-lanthana-doped alumina, baria-lanthana-neodymia-doped alumina, zirconia, lanthana-doped zirconia, yttria-doped zirconia, neodymia-doped zirconia, praseodymia-doped zirconia, titania-doped zirconia, titania-lanthana-doped zirconia, lanthana-yttria-doped zirconia, ceria, ceria-zirconia composite oxides, and rare earth stabilized ceria-zirconia composite oxides.
5. 3. The layered catalyst article of claim 1 or 2, wherein at least a portion of the platinum component and at least a portion of the rhodium component are together supported on one or more supports selected from ceria-doped alumina, ceria-zirconia composite oxides, and rare earth stabilized ceria-zirconia composite oxides.
6. 3. The layered catalyst article of claim 1 or 2, wherein at least 70% of said platinum component, preferably all of said platinum component, is supported on one or more supports along with at least a portion of said rhodium component in said top layer.
7. 3. The layered catalyst article of claim 1 or 2, wherein at least 10%, at least 30%, or at least 50% of the rhodium component is supported on one or more supports along with the platinum component in the top layer.
8. 3. The layered catalyst article of claim 1 or 2, wherein the palladium component is supported in said top layer and said bottom layer in a ratio, calculated as elemental palladium, of greater than 1:1 to less than or equal to 10:1, preferably in the range of 1.2:1 to 6:1, more preferably in the range of 1.5:1 to 4:1, and most preferably in the range of 2:1 to 4:
1.
9. a) a top layer comprising a palladium component, a platinum component and a rhodium component, the palladium component, the platinum component and the rhodium component being present in supported form, with all of the platinum component and at least a portion of the rhodium component being supported together on one or more supports selected from ceria-doped alumina, zirconia-doped alumina, ceria-zirconia-doped alumina, lanthana-zirconia-doped alumina, baria-lanthana-doped alumina, baria-lanthana-neodymia-doped alumina, zirconia, lanthana-doped zirconia, yttria-doped zirconia, neodymia-doped zirconia, praseodymia-doped zirconia, titania-doped zirconia, titania-lanthana-doped zirconia, lanthana-yttria-doped zirconia, ceria, ceria-zirconia composite oxides, and rare earth-stabilized ceria-zirconia composite oxides; b) a bottom layer comprising a palladium component in supported form as the sole platinum group metal component; and c) a substrate carrying the top layer and the bottom layer; Including, 3. The layered catalyst article of claim 1 or 2, wherein the palladium component is supported in a ratio, calculated as elemental palladium, in said top layer and said bottom layer in the range of from 1.2:1 to 6:1, preferably from 1.5:1 to 4:1, more preferably from 2:1 to 4:
1.
10. a) a top layer comprising a palladium component, a platinum component and a rhodium component, wherein the palladium component, all of the platinum component and the rhodium component are present in supported form, and all of the platinum component and at least a portion of the rhodium component are supported together on one or more supports selected from ceria-doped alumina, ceria-zirconia composite oxides, and rare earth stabilized ceria-zirconia composite oxides; b) a bottom layer comprising a palladium component in supported form as the sole platinum group metal component; and c) a substrate carrying the top layer and the bottom layer; Including, 3. The layered catalyst article of claim 1 or 2, wherein the palladium component is supported in said top layer and said bottom layer in a ratio, calculated as elemental palladium, in the range of from 1.5:1 to 4:1, preferably from 2:1 to 4:
1.
11. 3. The layered catalyst article of claim 1 or 2, wherein the mass ratio of the palladium component to the platinum component in the layered catalyst article, calculated as elemental palladium and platinum, is in the range of from 1:1 to 10:1, for example, from 2.0:1 to 9:1, from 2.1:1 to 6:1, or from 2.3:1 to 5:
1.
12. 3. The layered catalyst article of claim 1 or 2, wherein the bottom layer is applied onto the substrate and the top layer is applied onto the bottom layer without an intermediate layer.
13. 3. The layered catalyst article of claim 1 or 2, wherein the substrate is a flow-through substrate or a wall-flow substrate.
14. 3. A method of using the layered catalyst article of claim 1 or 2 for the reduction of hydrocarbons, carbon monoxide and nitrogen oxides in an exhaust gas stream.
15. 10. An exhaust gas treatment system comprising the layered catalyst article of claim 1 disposed downstream of an internal combustion engine, particularly a gasoline engine.
16. 16. The exhaust gas treatment system of claim 15, wherein the layered catalyst article is disposed downstream of an internal combustion engine in a close location, an underfloor location, or both.
17. 17. The exhaust gas treatment system of claim 15 or 16, wherein the layered catalyst article is followed directly or indirectly by a four-way catalytic converter.
18. 17. A method of treating an exhaust gas stream comprising contacting said exhaust gas stream with the layered catalyst article of claim 1 or 2 or the exhaust gas treatment system of claim 15 or 16.
19. 20. The method of claim 18, wherein said layered catalyst article is particularly useful for the reduction of hydrocarbons, carbon monoxide and nitrogen oxides in exhaust gas streams from internal combustion engines, particularly gasoline engines.